Exploring Trust/Mistrust in Journalistic Practice: An Actor-network Analysis of a Kenyan Newsroom. Issue 4 (2nd October 2021) - Wamunyu, Wambui
ABSTRACT: The entry of non-traditional actors into aspects of journalistic practice has been widely explored in scholarship, as have expressions of the public's trust in journalistic work. However, there is a scarcity of research addressing the construct of trust in relation to the interactions among traditional and non-traditional journalism actors engaged in news production. Through the use of actor-network theory and by applying qualitative case study design, this study focused on the nature of journalistic practice in a digitally disrupted Kenyan newsroom, and how trust/mistrust manifested itself within the actor-network of journalistic practice. Theoretical and thematic analyses established the social and technological actors that had joined the process of journalistic practice while four findings emerged addressing notions of trust/mistrust within the actor-network. These findings were as follows: trust occurs within an established routinized process; trust is enacted within a particular news media environment; new entrants in journalistic practice need to demonstrate value to gain trusted entry in the actor-network; and trust is engendered at institutional level but needs acceptance at individual level.